1993
DOI: 10.1017/s0950268800051025
|View full text |Cite
|
Sign up to set email alerts
|

The colonization of broiler chickens withCampylobacter jejuni: some epidemiological investigations

Abstract: Between June 1990 and July 1991, broiler chickens from 49 flocks from 23 farms were examined for the carriage of Campylobacter jejuni at slaughter. Thirty-seven flocks (76%) were campylobacter-positive. Prevalence of campylobacter-colonization was not associated with any of a variety of factors such as water source and broiler house floor structure. There was also no apparent seasonal variation in carriage. Investigations on one farm indicated that dipping boots in disinfectant before workers entered broiler h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
110
1
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 10 publications
17
110
1
4
Order By: Relevance
“…Intervention procedures against horizontal transmission have to be studied further and the effectiveness of strict hygienic practices during the whole production period, such as was described as being successful in small scale experiments by Van de Giessen and colleagues [12] and Humphrey and co-workers [22], should be evaluated on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention procedures against horizontal transmission have to be studied further and the effectiveness of strict hygienic practices during the whole production period, such as was described as being successful in small scale experiments by Van de Giessen and colleagues [12] and Humphrey and co-workers [22], should be evaluated on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Quinolone treatment should not be seen as a means to eradicate Campylobacter contamination from poultry flocks. Horizontal intervention procedures at the farm level have to be studied further, including large-scale experiments under field conditions into the effect of strict hygiene practices during the whole production period, as described in the successful smallscale experiments of Van de Giessen et al (34) and Humphrey et al (9). Special attention has to be given to the influence of different housing systems and effects of transport on…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Previous studies showed that Campylobacter spp. were recovered from 76% [11], 18% [13], 67% [12], or 57% [22] of flocks. It seems that the recovery rates differ from one country to another.…”
mentioning
confidence: 99%